2016
DOI: 10.4103/0366-6999.194641
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mutations in Myocilin and Beta-1,4-galactosyltransferase 3 Genes in a Chinese Family with Primary Open-angle Glaucoma

Abstract: Background:Glaucoma is a major cause of irreversible blindness worldwide. There is evidence showing that a subset of the disease is genetically determined. In this study, we screened for mutations in chromosome 1q-linked open-angle glaucoma (GLC1A) in a Chinese family with primary open-angle glaucoma (POAG).Methods:A total of 23 members from five generations of a family were enrolled and underwent thorough ophthalmologic examinations. In addition, 200 unrelated healthy Chinese controls were also recruited as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, a mutation C1456_T in MYOC gene was identified in a Chinese family. Beta-1, 4-galactosyltransferase 3 ( B4GALT3 ) gene also showed mutation at G322_A in this POAG family [ 137 ]. In a transgenic mouse model of POAG, MYOC mutation Y437_H shows a significant increase in IOP with abnormal extracellular matrix accumulation that potentially reduces aqueous outflow [ 136 ].…”
Section: Genes Associated With Glaucomamentioning
confidence: 99%
“…Recently, a mutation C1456_T in MYOC gene was identified in a Chinese family. Beta-1, 4-galactosyltransferase 3 ( B4GALT3 ) gene also showed mutation at G322_A in this POAG family [ 137 ]. In a transgenic mouse model of POAG, MYOC mutation Y437_H shows a significant increase in IOP with abnormal extracellular matrix accumulation that potentially reduces aqueous outflow [ 136 ].…”
Section: Genes Associated With Glaucomamentioning
confidence: 99%
“…This variant has a relatively high frequency in gnomAD (0.00002) for a rare autosomal dominant disease, and we speculate that it might have reduced penetrance. Two other MYOC missense variants, p.(Leu486Phe) and p.(Val402Ile), have been previously reported in non‐Finnish patients with glaucoma (Fingert et al, 1999; Huang et al, 2014; Liao et al, 2016), while the MYOC p.(Asp378Asn) is a novel variant, although a different pathogenic missense change at the same amino acid residue has been reported before in a Chinese patient with sporadic JOAG (Huang et al, 2014). JG059 and JG060, father and son, harboured this novel variant and were diagnosed with JOAG at the age of 15 and 29, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that MYOC Q368X constitutes the most frequent variation responsible for late-onset POAG development, with an average age of 59 years at the date of diagnosis, whereas the Y437H mutation is responsible for early-onset glaucoma with an average age of onset of 20 years [115]. Besides, it has been reported that C1456T mutation in MYOC was responsible for the POAG pathogenesis in the Chinese family [123].…”
Section: Rare Variants Of Genes With High Effect Size Correlated Withmentioning
confidence: 99%